Environmental education research in Brazil: some highlights from theses and dissertations - de Carvalho, Luiz Marcelo [UNESP]; Neto, Jorge Megid; Kawasaki, Clarice Sumi; Bonotto, Dalva Maria Bianchini [UNESP]; do Amaral, Ivan Amorosino; Fernandes, José Artur Barroso; Santana, Luiz Carlos [UNESP]; Carvalho, Maria Bernadete Sarti da Silva [UNESP]; Cavalari, Rosa Maria Feiteiro [UNESP] (Taylor & Francis, 2018)
This article discusses an analysis of abstracts of Brazilian theses and dissertations on environmental education from a database organised and maintained by a group of researchers in the EArt Project (www.earte.net). In presenting extracts of key trends in this dataset, our aim is to provide a snapshot of the many possible approaches to, and histories of, Brazilian environmental education research. The data also allow us to raise some questions that explore possible ‘blank spots’, ‘blind spots’ and ‘bald spots’ in Brazilian research on environmental education. Given the temporal development of the research field since the 1980s, we illustrate these ‘spots’ by exploring data related to epistemological and methodological diversity, from the viewpoint of knowledge areas as well as the graduate programmes that have been developing research on environmental education. Finally, we draw a picture of the methodological trends that have been privileged by Brazilian researchers, and pose questions as to what is needed in shaping an agenda for research on environmental education in Brazil into the future.
Keywords: Brazilian environmental education; environmental education research; methodological trends; postgraduate environmental education; theses and dissertations